Potential alternative drug treatment for bone giant cell tumor - Chen, Zhangxin; Zhang, Cong; Hong, Haisen; Xu, Wenbin; Sha, Mo; Ding, Zhenqi (Frontiers in Cell and Developmental Biology, 2023)
Background: Bone Giant-cell tumor (BGCT) is one of the world's major diseases of a locally aggressive bone tumor. In recent years the denosumab treatment has been introduced before curettage surgery. However, the current therapeutic was not always practical given the local recurrence effects. Due to the complex nature of BGCT, This study aims to use bioinformatics to identify potential genes and drugs associated with BGCT.